Characterization of the A subunit epitopes in immunogenicity and enterotoxicity of enterotoxigenic Escherichia coli (ETEC) heat-labile toxin - Huang, Jiachen (Kansas State University, 2017)
Heat-labile enterotoxin (LT) is one of the most important toxins produced by enterotoxigenic Escherichia coli (ETEC). It consists of one A subunit (LTA) for intracellular enzymatic activity and five B subunits (LTB) forming a pentamer for binding to host cell receptors. In the last few decades, LT has been extensively studied as a strong immune stimulator, as well as an effective adjuvant with multiple immunomodulatory properties. To understand better the features of LT, we mapped B-cell linear epitopes of the enzymatic A subunit and explored the relationship between these epitopes and the toxicity of LT. Eleven B-cell linear (continuous) epitopes were in silico identified based on online software. In part one of the study, all 11 epitopes were fused into a modified ovalbumin carrier protein respectively. Each recombinant fusion protein was expressed and purified, and was characterized in ELISA and Western Blot using the anti-LT serum. Moreover, each fusion protein was used to immunize mice to determine immune response specific to LT in vivo. A total of eleven epitopes were identified from the LTA subunit. Results showed that anti-LT serum recognized all 11 epitopes, while the mouse immunization study indicated that antibodies derived from epitope 7 (₁₀₅SPHPYEQEVSA₁₁₅) had significantly greater anti-LT antibody titers and neutralized LT enterotoxicity more efficiently than the other epitopes. In part two of the study, to test whether individual epitope plays a role in LT toxicity, 10 epitopes in the A1 domain of LTA subunit were replaced by a foreign peptide respectively and the mutant LTs were examined for enterotoxicity. Data indicated that all these LT mutants showed enterotoxicity abolished. However, these LT mutants formed holotoxin structure and bound to GM1 in vitro. Results from this study indicated that replacement of these LT epitopes did not affect the forming of LT holotoxin structure and the binding to host receptors, indicating LT can serve as a safe vaccine platform to carry foreign antigens. With the immunodominant epitope 7 being kept while other LTA epitopes replaced by epitopes from other ETEC virulence factors, this platform can be used to construct broadly protective multivalent mucosal vaccines against ETEC, and perhaps as a universal platform for vaccines against other enteric diseases.
Keywords: Enterotoxigenic Escherichia coli; Heat-labile toxin; Epitopes